Covid-19, capitalism and political elites: The real threat to humanity. Issue 2 (July 2021) - Alexiou, Constantinos
It has been more than a year since the Covid-19 outbreak in Wuhan, one of the largest cities in China. The global tsunami that followed took the bourgeois regimes across the globe by surprise heralding a new era of socioeconomic misery, suggesting that this multifaceted crisis could become the worst crisis in the history of capitalism. The inability of the current political system to deal with the Covid-19 pandemic became apparent from the very outset, hence exposing – in the most emphatic manner – the ills of the dominant market economy. In this opinion paper, we argue that society, as a global collective entity, has been reduced to an entity that obeys orders and dances to the rhythm set by international organizations. Furthermore, the severely restricted political and social rights might be a dress rehearsal of what the future holds for humanity.